The pedagogical approach of Ibn Sahnun as presented in his book Adab al-Mu’allimin - bezziou, ahmed (El Omda in Linguistics and Discourse Analysis, 2022)
The aim of this work, which deals with the pedagogical approach of Ibn Sahnun through his book Adab al-Mu‘allimin, is to delve into the contributions of early scholars in the field of education in order to enhance learners’ abilities. In this context, light is shed on Ibn Sahnun’s educational efforts, starting from his ideas presented in his compendium, which combines the curriculum, the characteristics and role of the teacher, and the discipline of the learner. He emphasizes a teaching method that begins with writing and discussion and leads to comprehension. At the same time, he focuses on the qualities of the teacher, including being admired by students, influencing them positively, embodying virtuous behavior and ethics, and demonstrating sincerity and patience in work. He also addresses teachers’ rights and school holidays. Ultimately, within his educational framework, he distinguishes between what is essential in the curriculum and what is not—namely, what is mandatory and what is optional.